RPP40 is a prognostic biomarker and correlated with tumor microenvironment in uterine corpus endometrial carcinoma - Tang, Jianming; Tian, Xiaoli; Min, Jie; Hu, Ming; Hong, Li (Frontiers in Oncology, 2022)
Ribonuclease P/MRP Subunit P40 (RPP40), a component of ribonuclease P and multimeric ribonuclease P complex, was reported as one of the promoting factors for chemoresistance of acute myeloid leukemia and recurrence predictor of early-stage triple-negative breast cancer. Whereas the functional role of RPP40 in uterine corpus endometrial carcinoma (UCEC) is unclear. In this study, comprehensive bioinformatic analyses were conducted to explore the predictive role of RPP40 on UCEC diagnosis and prognosis, as well as the underlying mechanism. Differential analyses of multiple databases showed that both mRNA and protein expression of RPP40 were significantly upregulated in UCEC tumor tissues. Besides, RPP40 mRNA expression level was significantly correlated with clinicopathological characteristics of UCEC patients, including clinical stage, primary therapy outcome, histological type, histologic grade, OS event, DSS event, and PFI event. Receiver operating characteristic (ROC) analysis showed RPP40 was a reliable predictor for UCEC diagnosis with an area under the curve (AUC) of 0.775, a sensitivity of 0.829, and a specificity of 0.719. Kaplan-Meier (KM), cox regression and nomogram analyses showed that high RPP40 expression was an independent prognostic factor for the 1-year, 3-year, and 5-year survival of UCEC patients. In addition, enrichment analysis of RPP40-associated differentially expressed genes (DEGs) and correlation analyses showed that the expression of RPP40 was correlated with the regulation of extracellular matrix (ECM) and immune cell inﬁltration. In conclusion, upregulation of RPP40 is significantly correlated with poor survival and tumor microenvironment of UCEC, suggesting that RPP40 is a promising biomarker of poor prognosis and a potential target of chemotherapy or immunotherapy in UCEC.